Issues for Long-Range Projection of International Energy Markets Through the Prism of Sustainable Development - Guliyev, Igbal; Litvinyuk, Igor (International Journal of Energy Economics and Policy, 2017)
Modern energy system development model requires incorporation of not only demand and supply sides of energy markets, but also reference of new technologies deployment throughout the whole value chain, governmental policies in place, and other non-market indicators that, however, provide for the whole market equilibration by indirect energy resources price regulation. Consequently, overcoming the traditional framework is getting basic precondition for achieving sustainable development in the energy sector, covering the whole energy system for research purposes due to global and coherent transition from forecasting of energy development to constructing of new alternatives and creating a new world which meet the goals of sustainable development. The next step will be a creation of ways of their achievement, and management systems, which allows countries, regions and the whole world to stay on that pathway. The article comes up with suggestions on making alterations to the current practice of energy systems forecasting process. Keywords: scenarios, sustainable development, international relations, global energy markets JEL Classifications: O13, P28, Q47, Y3